(untitled) (Research, Society and Development, 2023)
Objective: To discuss and highlight in the literature the determining factors of non-adherence of elderly patients with RAS to drug therapy, potentiated by the COVID pandemic 19. Material and method: This is a literature review that aims at the analysis and synthesis of the determining factors for the non-adhering of the elderly with hypertension to drug treatment. We analyzed the publications produced between 2017 and 2022, with full texts and available in the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Google Scholar, in addition to the manual of the 7th Brazilian Guidelines on Arterial Hypertension and the World Health Organization (WHO). Results: The search in the databases resulted in the identification of 1,203 articles. After the final reading, 32 articles were selected that contemplated the objectives discussed in the development of this work. Final considerations: It was found that many factors interfere with the non-adherence of the elderly to drug therapy, factors that are linked to the elderly and the health system, as the patient presents difficulties in following the proposed therapeutic scheme, either due to its complexity, forgetfulness, adverse effect of the drug and its belief in alternative empirical drugs.